Integrated pathogen load and dual transcriptome analysis of systemic host-pathogen interactions in severe malaria - Lee,HJ; Georgiadou,A; Walther,M; Nwakanma,D; Stewart,L; Levin,M; Otto,T; Conway,D; Coin,L; Cunnington,A (Science Translational Medicine, 2018)
The pathogenesis of infectious diseases depends on the interaction of host and pathogen. In Plasmodium falciparum malaria, host and parasite processes can be assessed by dual RNA-sequencing of blood from infected patients. Here we performed dual transcriptome analyses on samples from 46 malaria-infected Gambian children to reveal mechanisms driving the systemic pathophysiology of severe malaria. Integrating these transcriptomic data with estimates of parasite load and detailed clinical information allowed consideration of potentially confounding effects due to differing leukocyte proportions in blood, parasite developmental stage, and whole-body pathogen load. We report hundreds of human and parasite genes differentially expressed between severe and uncomplicated malaria, with distinct profiles associated with coma, hyperlactatemia, and thrombocytopenia. High expression of neutrophil granule-related genes was consistently associated with all severe malaria phenotypes. We observed severity-associated variation in the expression of parasite genes which determine cytoadhesion to vascular endothelium, rigidity of infected erythrocytes, and parasite growth rate. Up to 99% of human differential gene expression in severe malaria was driven by differences in parasite load, whereas parasite gene expression showed little association with parasite load. Co-expression analyses revealed interactions between human and P. falciparum, with prominent co-regulation of translation genes in severe malaria between host and parasite. Multivariate analyses suggested that increased expression of granulopoiesis and interferon-γ related genes, together with inadequate suppression of type-1 interferon signalling, best explained severity of infection. These findings provide a framework for understanding the contributions of host and parasite to the pathogenesis of severe malaria and identifying targets for adjunctive therapy.